(untitled) (Gaceta Técnica, 2026)
This research promotes industrial innovation and the development of sustainable infrastructure with an emphasis on environmental protection. Its main goal was to improve the stability of sandy soils used for subgrades through the combined use of lime, coconut fibers, and recycled bricks. An applied methodology with a quantitative approach was employed, based on a quasi-experimental design and a hypothetical-deductive scientific method at an explanatory level. The sample consisted of sandy soils from three test pits, 1.5 m deep, located on Av. Los Jazmines – Pachacámac, distributed between km 0,191+ and km 0,394+. The soils were classified into a control group and four experimental groups following a 23-1 fractional factorial design. The results demonstrated that the incorporation of the stabilizing materials significantly improves the mechanical properties of the soil, contributing to the implementation of more durable and environmentally friendly infrastructure